KOMUNIKASI TERAPEUTIK ANTARA TERAPIS DAN ANAK PENYANDANG DOWN SYNDROME DALAM MENINGKATKAN KEMANDIRIAN DI SEKOLAH DASAR LUAR BIASA FAJAR AMANAH KECAMATAN TUALANG KABUPATEN SIAK - Roby Juliasmara; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Down syndrome is one of the diseases caused by genetic disorders that have an impact on physical and mental retardation so that it takes a special action so that they can be independent. Independence is one of the attitudes that must be possessed by Down syndrome children and can be obtained through special institutions or foundations, one of which is the Fajar Amanah Extraordinary School (SLB) in Tualang District. In the process, the therapist uses several special methods to restore the child's physical and behavioral conditions. In the therapeutic process, it is known that the therapist uses therapeutic communication. The purpose of this paper is to look at the phases of therapeutic communication applied at the Fajar Amanah SLB in Tualang District, Siak Regency. This study uses qualitative writing methods. The research was conducted at the Fajar Amanah Extraordinary School (SLB) on Jl. Wakaf KM 6.5 Tualang. The selection of informants is done by purposive technique. The informants from this study were a doctor, two therapists, and three parents. Data collection techniques used were interviews, observation, and documentation. While the validity of the data used in this study is an extension of participation and triangulation. The results showed that the therapist in the process of carrying out therapeutic communication to children with Down syndrome in the Fajar Amanah SLB in Tualang District, Siak Regency was carried out through several stages. In the pre-interaction phase, it is known that therapists design ways to build interpersonal communication with parents and use several methods such as identification, assessment / assessment, and briefings in gathering all information related to the child's physical condition. In the orientation phase, the therapist provides a safe and comfortable situation for the child by applying three basic features of therapeutic communication. In the working phase, the therapist begins to carry out the therapeutic process using special methods and is accompanied by several therapeutic communication techniques to increase the independence of children with Down syndrome. In the termination phase, the therapist only gives advice or advice to parents about how to care for children at home.Keywords: Therapeutic Communication, Down Syndrome, Independence